Principles of capitalistic commodity production: a rejoinder - Fritz Helmedag (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
Reich (2013) recapitulates my model (Helmedag 2012a) incorrectly. Above all, he mixes up exogenous with endogenous variables. Moreover, Reich's interpretation of the system's dynamics is on the one hand formally insufficient; on the other hand, matters are presented in a more complicated way than necessary.
Keywords: A10; B12; E10; 330; effective demand; employment; income shares; labour theory of value; rate of profit